2006
DOI: 10.1080/15287390500470759
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Estradiol, Ethinylestradiol and Octylphenol Affect Survival and Growth ofRana pipiens and Rana sylvaticaTadpoles

Abstract: Endocrine disrupting compounds (EDCs) are often detected in the aquatic environment and can negatively affect the health of wildlife populations. However, little is known about the sensitivity of native amphibians to EDCs. Wood frogs (Rana sylvatica) and Northern leopard frogs (Rana pipiens) were exposed to three estrogenic EDCs: estradiol (E2), ethinylestradiol (EE2), and 4-tert-octylphenol (OP). In addition, R. pipiens were exposed during two developmental stages (Gosner stages 26 and 36) to examine life-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 79 publications
0
15
1
1
Order By: Relevance
“…The greatest LOEC value for Japanese medaka responding to E2 was 1,000-fold greater than the least LOEC. Some other effects, such as lethality to crustaceans and fish, growth of amphibian tadpoles, and development of copepod, were reported in the literature, and the NOEC or LOEC values associated with them were generally at mg/L level (Forget-Leray et al 2005;Hogan et al 2006;Rang et al 2003;Hirano et al 2004;Kashiwada et al 2002). Thus, it can be concluded that the reproductive endpoint is most sensitive for assessing the effect of E2 on aquatic organisms.…”
Section: Reasonableness Of Pnecsmentioning
confidence: 79%
“…The greatest LOEC value for Japanese medaka responding to E2 was 1,000-fold greater than the least LOEC. Some other effects, such as lethality to crustaceans and fish, growth of amphibian tadpoles, and development of copepod, were reported in the literature, and the NOEC or LOEC values associated with them were generally at mg/L level (Forget-Leray et al 2005;Hogan et al 2006;Rang et al 2003;Hirano et al 2004;Kashiwada et al 2002). Thus, it can be concluded that the reproductive endpoint is most sensitive for assessing the effect of E2 on aquatic organisms.…”
Section: Reasonableness Of Pnecsmentioning
confidence: 79%
“…Species commonly seen in laboratories include R. catesbeiana, the bullfrog, and R. pipiens, the northern leopard frog. Rana species were used early in developmental studies (Briggs and King 1952); today they play a key role in investigating endocrine disrupters and environmental toxins (Cassano et al 2006;Hogan et al 2006;Mikkelsen and Jenssen 2006). Rana are used extensively in physiology research, both as animal models (King 1998;Zayas et al 2004) and as subjects in their own right (Feder and Burggren 1992;Pryor and Bjorndal 2005).…”
Section: Frog Species and Common Research And Teaching Areasmentioning
confidence: 99%
“…Entre os consumidores secundários, a espécie mais sensível foi a truta-arcoíris (Oncorhynchus mykiss), um peixe que quando exposto à concentração de 0,00042 µg L -1 , na idade adulta, apresentou efeitos bioquímicos e genéticos relativos à qualidade e maturação dos gametas (Lahnsteiner et al 2006). As espécies menos sensíveis foram as rãs Rana pipiens e Rana sylvatica, que apresentaram efeitos no desenvolvimento quando submetidas à 1362 µg L -1 em período de metamorfose (Hogan et al 2006).…”
Section: Ecotoxicidadeunclassified